1999
DOI: 10.1007/pl00010259
|View full text |Cite
|
Sign up to set email alerts
|

Addition von enantiomerenreinen Aminen an aktivierte Olefine, 2. Mitt. Über die Addition an (E)-4-Oxo-4-phenyl-2-butensäure-ethylester

Abstract: Zusammenfassung. Die Addition von (S)-Phenethylamin an (E)-4-Oxo-4-phenyl-2-butensa Èureethylester verla Èuft ohne kinetische Selektivita Èt. Addiert man hingegen (S)-Alaninisopropylester beziehungsweise benzylester, ist das nach der b,pl,H-Regel als AB-beziehungsweise BB-Produkt zu bezeichnende Diastereomere kinetisch bevorzugt. Bei der Addition von (S)-Alaninbenzylester ist im Unterschied zu den anderen und fru Èher untersuchten Beispielen das BB-Produkt gegenu Èber dem AB-Produkt thermodynamisch nicht bevor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, crystallization of (S,S)-121 was coincidental and, as later revealed, structurally related compounds afforded oily diastereomeric mixtures. [100] We assumed that using free carboxylic acids as Michael acceptors rather than esters would afford crystalline amino acid products. Our initial studies were interrupted by a publication coming from a Kaneka group, which reported CIDT starting from aroylacrylic acids 122 a-g (Scheme 45A).…”
Section: Aza-michael and Mannich-type Reactionsmentioning
confidence: 99%
“…However, crystallization of (S,S)-121 was coincidental and, as later revealed, structurally related compounds afforded oily diastereomeric mixtures. [100] We assumed that using free carboxylic acids as Michael acceptors rather than esters would afford crystalline amino acid products. Our initial studies were interrupted by a publication coming from a Kaneka group, which reported CIDT starting from aroylacrylic acids 122 a-g (Scheme 45A).…”
Section: Aza-michael and Mannich-type Reactionsmentioning
confidence: 99%
“…Secondary alkyl-aryl-carbinols exhibited a significant predictive enantiomer-selectivity in acetal formation under reversible conditions with the designed lactols [ 41 , 42 , 43 , 44 ]. The effect of enantiomer selectivity was also observed in ether formation [ 45 , 46 ], thioacetal and thioether formation [ 47 ] and in 1,4-addition of amines [ 48 , 49 ]. Added steric hindrance led to increased enantiomer selectivities of up to 14:1 [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%